1989
DOI: 10.1104/pp.89.4.1207
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Pea Mitochondrial Pyruvate Dehydrogenase Complex

Abstract: Inactivation of the pyruvate dehydrogenase complex catalyzed by pyruvate dehydrogenase kinase was studied using intact mitochondria purified from green leaf tissue of pea (Pisum sativum L.) and dialyzed mitochondrial extracts. Thiamine pyrophosphate was inhibitory in dialyzed extracts but not in intact mitochondria, except in the presence of high concentraffons of Na+. NH4+, at concentrations as low as 20 micromolar, markedly stimulated inactivation in dialyzed extracts. K+ in the range I to 10 millimolar also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…In this paper, we characterize further the mechanism involved in the monovalent cation stimulation and show that NH4+ stimulation of PDH kinase activity persists in the presence of saturating Kf. This latter result supports our hypothesis that photorespiratory NH4+ may be important in regulating PDC activity during photosynthesis and photorespiration (Schuller and Randall, 1989).…”
supporting
confidence: 81%
See 3 more Smart Citations
“…In this paper, we characterize further the mechanism involved in the monovalent cation stimulation and show that NH4+ stimulation of PDH kinase activity persists in the presence of saturating Kf. This latter result supports our hypothesis that photorespiratory NH4+ may be important in regulating PDC activity during photosynthesis and photorespiration (Schuller and Randall, 1989).…”
supporting
confidence: 81%
“…It was consistently observed that at subsaturating concentrations of ATP, kinase activity in the presence of K+ was less than in the presence of NH4+. Previous studies by Schuller and Randall (1989) demonstrated that NH4+ and K+ had no effect on PDC activity even at concentrations up to 100 mM; therefore, the monovalent cation effects described here are on the kinase activity .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Plants are unique in having an additional isoform of PDC in their plastids (10,11) that is also quite sensitive to product feedback regulation but does not undergo regulation by reversible phosphorylation (10,27). In vitro studies of the PDC kinase have also shown that the phosphorylation-inactivation reaction is stimulated by micromolar NH4+ (29) and is inhibited by pyruvate, the substrate for the PDC (26,30). In situ studies with purified pea leaf mitochondria have shown that the PDC phosphorylation status is increased when the mitochondria are oxidizing substrates other than pyruvate (6), in particular, glycine, an intermediate of the photorespiratory carbon oxidation pathway.…”
mentioning
confidence: 99%